Physico-enzymatic characteristics of cervical mucus with reference to fertility in repeat breeder cows - SELVARAJU, P; KUMAR, HARENDRA; MAHMOOD, S (The Indian Journal of Animal Reproduction, 2023)
The higher occurrence of turbid CM and atypical fem pattern was observed in RB cows. Both ACP and AKP in estrual CM were significantly (P<0.01) higher in normal than RB cows and also in pregnant than nonpregnant. A lower level of plasma progesterone was observed at estrus in most of the pregnant RB cows which exhibited higher percentage of typical fem pattern in cervical mucus.